THINKING ABOUT THE COMPETENCE AND PERFORMANCE OF THE NURSING FACULTY - Virginia Visconde Brasil; Celi Cristiane Pereira de Alencar; Ivone Mucci (Universidade Federal do Paraná, 1996)
The discussion about the learning and teaching process was always in the discussion of those who care quality have been criticized. The teaching graduate professionals with a scientific knowledge, technical abilities an attributes that are sometimes not entailed with the work's reality. The legal concerns about nursing teaching are no specific about what kind of teachers is necessary for undergraduate level, and during graduation the student does not receive enough information to subsidize a possible teaching activity. When we think about nursing teaching we consider that are many pedagogical options adopted and its choice is related to the finality the teacher's gives to his work, as well as the school policy and each teacher's particular characteristics. The teacher's pedagogical option has influence on the students critical preparation and in their values and habits - important components to the construction of a new society. We perceive, however, that the nursing teachers seem not to be prepared to develop in the students the critical thinking, since they were not prepared for it the specific didatical and pedagogical preparation would contribute to a better teaching performance. To be a competent professional may not mean necessarily be a good nursing teacher.